2017
DOI: 10.1590/0103-8478cr20160078
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy in the estimates of zucchini production related to the plot size and number of harvests

Abstract: The productive variability in horticultural crops affects the planning and quality of the experiments, inflating the error and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 10 publications
0
8
0
1
Order By: Relevance
“…This situation occurs due to the uneven maturation of the fruits due to physiological characteristics and the growth habit. This means that the researcher needs to harvest the staggered production and, in some of these harvests, the plant may not have fruit or present fruit not suitable for harvest (Cargnelutti Filho et al, 2004;Lúcio & Benz, 2017). The immediate consequence of this situation is the RESUMO Uma abordagem para avaliações de experimentos para culturas de múltiplas colheitas baseado em regressão não linear Modelos de crescimento de base biológica podem ser uma alternativa na identificação da resposta produtiva de hortaliças de múltiplas colheitas.…”
Section: Invited Articleunclassified
“…This situation occurs due to the uneven maturation of the fruits due to physiological characteristics and the growth habit. This means that the researcher needs to harvest the staggered production and, in some of these harvests, the plant may not have fruit or present fruit not suitable for harvest (Cargnelutti Filho et al, 2004;Lúcio & Benz, 2017). The immediate consequence of this situation is the RESUMO Uma abordagem para avaliações de experimentos para culturas de múltiplas colheitas baseado em regressão não linear Modelos de crescimento de base biológica podem ser uma alternativa na identificação da resposta produtiva de hortaliças de múltiplas colheitas.…”
Section: Invited Articleunclassified
“…The most effective and also most used strategies to improve the quality of experiments with vegetables with multiple harvests are, namely, identification of crop-specific plot (Table 1) and sample sizes; determining the variability behavior between rows and between harvests, and; the study of data transformation and the use of Papadakis method to minimize the effects of excess zeros causing overdispersion in the database (Lúcio et al, 2011(Lúcio et al, , 2016Santos et al, 2012Santos et al, a,b, 2014Benz et al, 2015;Lúcio & Benz, 2017).…”
Section: Reducing the Variability In Vegetable Cropsmentioning
confidence: 99%
“…Studies in several vegetables have shown that harvest clustering reduces the variability between plants, decreasing data dispersion, and mitigating the negative effect of excess zeros in the database (Carpes et al, 2008(Carpes et al, , 2010Lúcio et al, 2011Lúcio et al, , 2016Santos et al, 2012Santos et al, a,b, 2014Benz et al, 2015;Lúcio & Benz, 2017). However, even with harvest clustering, variability may go on increasing, as the cumulative value of harvest "n" remains the same as that observed in harvest "n-1", when there are no products to be harvested in a plant, while in another, in which there are harvestable products, the value increases.…”
Section: Reducing the Variability In Vegetable Cropsmentioning
confidence: 99%
“…The experimental design aims to ensure the experimental accuracy and credibility of the results generated by the research (Lúcio & Benz, 2017). Correct choice of plot size is an important step of experimental planning aiming at increasing the accuracy and reliability of the results generated in the experiments and, at the same time, reducing the use of material, financial and human resources (Lúcio et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The estimation of plot size is based on uniformity trials without treatments (Schwertner et al, 2015a;Schwertner et al, 2015b) and depends directly on the magnitude of the experimental variability (Lúcio & Benz, 2017). The variability of the data in multiple-harvests horticultural crops, such as Solanum melongena L., is related to several factors such as (i) heterogeneity of soil fertility; (ii) intensive management; (iii) uneven application irrigation and fertilizers; (iv) occurrence of pests, diseases, and weeds; (v) uneven maturity of fruits; (vi) presence or absence of suitable fruits to be harvested in a given harvest (Lúcio & Sari, 2017;Krysczun et al, 2018).…”
Section: Introductionmentioning
confidence: 99%